2015
DOI: 10.1097/grf.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Management of Urologic Injuries With Laparoscopic Hysterectomy

Abstract: Injuries to the urinary tract during laparoscopic hysterectomy are quite rare, but are among the most serious injuries that occur during gynecologic surgery. Injury rates among subtypes of laparoscopic hysterectomy have been found to be similar. The most effective way to avoid urinary tract injury is knowledge of urinary tract anatomy and careful and thoughtful dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…Regarding intra- and post-operative complications, our results differ from those in the literature, particularly in terms of the risk of urinary tract injuries. Some authors have observed a higher incidence of urinary tract injuries with laparoscopic than with AH ( 23 ). Janssen et al .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding intra- and post-operative complications, our results differ from those in the literature, particularly in terms of the risk of urinary tract injuries. Some authors have observed a higher incidence of urinary tract injuries with laparoscopic than with AH ( 23 ). Janssen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, bladder injuries were detected and repaired early, in accordance with the literature. If there is a history of urinary tract surgery, computed tomography or magnetic resonance imaging may be very helpful to refrain bladder injury 12 . If there is any doubt about anatomy, intra‐operative consultation may be requested from urologist 12 .…”
Section: Discussionmentioning
confidence: 99%
“…If there is a history of urinary tract surgery, computed tomography or magnetic resonance imaging may be very helpful to refrain bladder injury 12 . If there is any doubt about anatomy, intra‐operative consultation may be requested from urologist 12 . Bladder bounds can be controlled intraoperatively by filling the bladder using a foley catheter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the greater breadth of pathology and tendency to use electrosurgery that may lead to delayed thermal damage in laparoscopic surgery. 1 Recently, the evidence showed the overall injury rate for laparoscopic hysterectomy was 0.73%, which did not appear to differ from the abdominal approach. Bladder injury rate ranged 0.05-0.66% and the ureteral injury rate ranged 0.02-0.4%.…”
Section: Introductionmentioning
confidence: 99%